ANALISIS RASIO KEUANGAN DAERAH UNTUK MENILAI KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN SIDOARJO (PERIODE TAHUN 2014 – 2018) - Widyanto, M. Yoga Susilo; Arief, Sjamsul (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2020)
The purpose of this study was to assess the financial performance of the Sidoarjo Regency Government using the Financial Ratio, the data used was the Sidoarjo Regency APBD in 2014 - 2018. This research method used 5 aspects of the Regional Financial Ratio, namely: 1) PAD Effectiveness Ratio, 2) Ratio Efficiency, 3) Regional Financial Independence Ratio, 4) Growth Ratio, 5) Harmony Ratio. The results of data analysis obtained an average of each regional financial ratio along with the criteria, namely; Effectiveness ratio of average PAD of 118.75%, Average Efficiency Ratio of 102.15%, Ratio of Regional Financial Independence on average of 59.67%, Growth Ratio there are 4 ratings namely: 1) average PAD growth of 7.20%, 2) Average income growth of 7.87%, 3) Operational Expenditures average growth of -8.21%, 4) Capital Expenditures average growth of 26.67%, Ratio There are 2 points in harmony, namely Capital Expenditures and Operational Expenditures, Capital Expenditures averaged 44.27% while Operational Expenditures amounted to 55.73%. The conclusion was obtained that the Regional Financial Performance of Sidoarjo Regency viewed from 5 aspects of ratio calculation. The PAD0 Effectiveness Ratio is said to be Effective, then the Efficiency Ratio which is said to be 2014-2015 is inefficient and 2016 to 2018 efficient, the Regional Financial Independence Ratio is said to be Participatory, the Growth Ratio which records a plus only for minus Operational Expenditures, and the Correlation Ratio that is said to be harmonious. Keywords: PAD Effectiveness Ratio, Efficiency Ratio, Regional Financial Independence Ratio, Growth Ratio, Efficiency Ratio